Coping with accommodation stress by female students in Nigerian Universities (2001)
Female students in Nigerian Universities face some problems. Some of the problems are peculiar to them. The problems include erratic power failure, inadequate supply of water, over-crowding, poor facilities and poor and inadequate transport facilities. The female students have devised coping strategies to deal with the problems. These include, the use of lamps and candles, using independent contractors to carry out repairs, and personal acquisition of some amenities. This has its effects, which include frequent students unrest, anti-social behavior, fire outbreak and health hazards. The paper recommends that adequate funding, provision of good transport facilities and the establishment of an efficient housing bureau are ways of finding a solution to the problems.